Explore the Predictive Value of Peripheral Blood Cell Parameters in Refractory Mycoplasma pneumoniae Pneumonia in Children Over 6 Years Old - Ling, Yaoyao; Ning, Jing; Xu, Yongsheng (Frontiers in Pediatrics, 2021)
Abstract Background: To determine the predictive value of peripheral blood cell parameters for refractory Mycoplasma pneumoniae pneumonia (RMPP) in children over 6 years old. Methods: A retrospective study was conducted in children with RMPP admitted to the respiratory department of Tianjin Children's Hospital from September 2017 to September 2019 and non-refractory Mycoplasma pneumoniae pneumonia (NRMPP) were selected by propensity score method and matched according to the ratio of 1:1.5.We analyzed the differences of clinical characteristics, peripheral blood cell parameters, imaging findings, and treatments between the two groups, and further determined the predictive value of peripheral blood cell parameters on RMPP. Results: There were 76 patients in the RMPP group and 114 patients in the NRMPP group. We found the RMPP group have a longer clinical course, and a higher incidence of intrapulmonary and extrapulmonary complications(P<0.01). Moreover, the proportion of children in the RMPP group who received immunotherapy (such as glucocorticoid, gamma immunoglobulin) and fiberoptic bronchoscopy intervention was higher than that in the NRMPP group(P<0.01). Meanwhile, the level of neutrophil, neutrophil/lymphocyte (NLR), platelet count/lymphocyte (PLR), mean platelet volume/lymphocyte (MPVLR), C-reactive protein (CRP), Lactic dehydrogenase (LDH) and Interleukin (IL)-6 in the RMPP group were significantly higher (P<0.01) than those in the NRMPP group. The incidence of pulmonary consolidation, atelectasis, and pleural effusion was also higher in the RMPP group (P<0.05). ROC curve and binary logistic regression analysis showed that NLR>3.92 (OR=3.243; 95%CI=1.485-7.081;P=0.003), MPVLR>5.29 (OR=2.700; 95%CI=1.258-5.795; P=0.011) and pleural effusion (OR=3.023; 95%CI=1.424-6.420; P=0.004) were significant factors in predicting RMPP. And our study showed that NLR had higher accuracy in predicting RMPP than CRP. Conclusions: The parameters of peripheral blood cells might be a predictor of RMPP. NLR>3.92, MPVLR>5.29 and pleural effusion might have important predictive value for RMPP in children over 6 years old.